Investigations on Gas Sensing and Energy Storage Applications of NiCo2O4 - Khushboo Gupta; Manish Kumar; Mohit Verma; O. P. Thakur (ECS Sensors Plus)
This study investigates NiCo _2 O _4 (NCO) as a material for both the functional detection of NH _3 gas and for energy storage applications. The cubic spinel phase of NCO is confirmed by powder X-ray diffraction pattern and field-emission scanning electron microscopy. Impedance spectroscopy studies reveal dielectric properties including permittivity, AC conductivity, and resistance across a frequency range of 10 Hz –1 MHz and temperature from 305 K–473 K. The highest AC conductivity, 3.04 × 10 ^–3 S m ^−1 , was recorded at 473 K, while Nyquist plots indicate superior ionic conduction at lower temperatures. The electrochemical analysis highlights both faradic and pseudocapacitive charge storage mechanisms, with a specific capacitance (Cs) of 339.51 F g ^−1 at 2 A g ^−1 . Low ionic resistance (3.93 Ω) and charge-transfer resistance (8.36 Ω) emphasize NCO’s high capacitive behavior. The NH₃ sensing performance of NCO nanoparticles showed rapid response and recovery times of 20 s and 18.6 s, respectively, at 60 ppm concentration under room temperature conditions. Density functional theory suggests bandgap of 1.90 and 0.44 eV for spin-up and spin-down states. The QC of 931 μF cm ^−2 is calculated at −0.73 V using the density of states which confirms the potential of NCO for energy storage applications. These combined experimental and theoretical findings underscore the dual-functional nature of NCO for integrated gas sensing and energy storage technologies.